2020
DOI: 10.1111/psyg.12577
|View full text |Cite
|
Sign up to set email alerts
|

A case of concomitant dementia with Lewy bodies and argyrophilic grain disease with prominent psychiatric symptoms

Abstract: Demented people frequently show behavioural and psychiatric symptoms, including agitation, aggression, depression, anxiety, irritability, disinhibition, hallucination and delusion, which are collectively referred to as behavioural and psychological symptoms of dementia (BPSD). In some cases, these individuals be admitted to a psychiatric hospital because of the appearance or exacerbation of BPSD. However, even after admission, BPSD affect their quality of life. It is therefore important to clarify the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Sekine et al reported an autopsy case of TLBD with panic attacks at the age of 81. 77 She was referred to a psychiatrist at the age of 83 years and diagnosed with a panic disorder. The patient's cognitive decline gradually progressed until the patient's death at the age of 85.…”
Section: Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekine et al reported an autopsy case of TLBD with panic attacks at the age of 81. 77 She was referred to a psychiatrist at the age of 83 years and diagnosed with a panic disorder. The patient's cognitive decline gradually progressed until the patient's death at the age of 85.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…The patient exhibited auditory and visual hallucinations at 79 years of age before cognitive decline appeared. Sekine et al reported an autopsy case of TLBD with panic attacks at the age of 81 77 . She was referred to a psychiatrist at the age of 83 years and diagnosed with a panic disorder.…”
Section: Clinical Profiles Of Psychiatric‐onset Prodromal Dlbmentioning
confidence: 99%